MELATIH KEPERCAYAAN DIRI SANTRI UNTUK MENGHADAPI DUNIA INDUSTRI 5.0 DI YAYASAN DARUL FURQON RAMADHAN BOGOR - Novia, Lisa; Nurhayati, Nurhayati; Desthianti, Unik; Anggraini, Katry; Wahidah, Nur Rachmah (LPPM Universitas Pamulang, 2020)
Darul Furqon Ramadhan Foundation Bogor has several obstacles in training students' self-confidence including inadequate infrastructure so that students' mastery of technology is still lacking, students' lack of competence in terms of technology mastery, students cannot recognize their strengths and competencies so they have low self confidence and afraid to make mistakes for example when expressing opinions in discussion forums or presentations they tend to be passive. It is recommended to the foundation to coordinate with parents in educating students, especially in terms of building self confidence, the foundation with educators collaborate and coordinate to strengthen the curriculum that prioritizes character education, the foundation strives to cooperate with various parties to improve technological facilities and infrastructure in facing and dealing with industry 5.0 by redesigning the curriculum used by adjusting to the curriculum of the Ministry of Education and Culture which considers the five potentialities